Specific stereochemistry of OP-1074 disrupts estrogen receptor alpha helix 12 and confers pure antiestrogenic activity - S. W. Fanning (Nature Portfolio, 2018)
Estrogen receptor alpha (ERα) plays critical roles in the etiology and treatment of breast cancer. Here the authors synthesize benzopyrans with variable side chains to identify antiestrogenic compounds and characterize OP-1074, a compound that exhibits pure antiestrogenic activity by inducing the degradation of ERα and possesses greater potency than tamoxifen or fulvestrant in a xenograft model.